Annual volume and distribution of physical training in Norwegian female cross-country skiers and biathletes: A comparison between sports, competition levels, and age categories—The FENDURA Project - Osborne, J. O.; Solli, G. S.; Engseth, T. P.; Welde, B.; Morseth, B.; Noordhof, D. A.; Sandbakk, Ø.; Andersson, E. P. (International Journal of Sports Physiology and Performance, 2024)
Purpose: To describe and compare the annual physical training characteristics between Norwegian female cross-country (XC) skiers and biathletes across competition levels and age categories.